The pro-fibrotic role of autophagy in renal intrinsic cells: mechanisms and therapeutic potential in chronic kidney disease - Zhang, Ying-Ying; Zhou, Xiao-Tao; Huang, Geng-Zhen; Liao, Wen-Jun; Chen, Xian; Ma, Yue-Rong (Frontiers in Cell and Developmental Biology, 2024)
Chronic kidney disease (CKD) represents a significant global public health burden, affecting over 10% of the world’s population. Its high morbidity, multifactorial complications, and substantial mortality impose significant burdens on healthcare systems and patients, necessitating considerable investment in healthcare resources. Renal fibrosis (RF) is a key pathological feature and driver of CKD progression. Extensive research indicates that autophagy participates in the complete pathogenesis of RF. Under physiological conditions, autophagy is essential for maintaining renal cellular homeostasis. However, under pathological conditions, perhaps aberrant and sustained activation of autophagy contributes to oxidative stress, apoptosis, inflammation, etc. Ultimately, they accelerate the development of RF. The role of autophagy in RF is currently controversial. This review investigates the molecular mechanisms by which intrinsic renal cell autophagy contributes to RF across diverse disease models, suggesting that autophagy and its associated regulatory pathways represent potential diagnostic and therapeutic targets for CKD.